On the geometrical interpretation of scale-invariant models of inflation - Karananas, Georgios; Rubio, Javier (Physics letters, 2016)
We study the geometrical properties of scale-invariant two-field models of inflation. In particular, we show that when the field-derivative space in the Einstein frame is maximally symmetric during inflation, the inflationary predictions can be universal and independent of the details of the theory.
Gesehen am 07.05.2020